OTHELLO’S VERBAL DEFENCE: DISTORTING REALITY IN SHAKESPEARE’S OTHELLO - Rizky Setyaningrum (Center of Language and Cultural Studies [CLCS], 2018)
The study describes Othello’s verbal defences by means of Perry London’s Verbal Defences theory as reflected in William Shakespeare’s Othello, the Moor of Venice. The study was a content analysis whose primary data were words, phrases, sentences and dialogues in the play. The secondary data were articles discussing the Othello, the Moor of Venice. Data were analyzed through determining Othello’s arguments on ego verbal defence mechanisms using Perry London’s Verbal Defences theory. This study revealed that three elements of verbal defences, namely, emotional insulation, intellectualization, and rationalization are experienced by Othello. They operate unconsciously and these mechanisms neutralize the upsetting impact of threatening ideas by distorting reality. In distorting reality, ego takes some extreme ways. One of those ways is “talking away” the anxiety stimuli as well as by the other means of obscuring and retreating from reality.